Comparison of 50- and 66-Gy total irradiation doses for postoperative cervical treatment of patients with oral squamous cell carcinoma. (August 2020) - Hirai, Hideaki; Ohsako, Toshimitsu; Kugimoto, Takuma; Tomioka, Hirofumi; Michi, Yasuyuki; Kayamori, Kou; Yoda, Tetsuya; Miura, Masahiko; Yoshimura, Ryoichi; Harada, Hiroyuki
Highlights: Doses of 50 and 66 Gy for postoperative cervical irradiation were compared. Cervical control rate was not significantly different between the irradiation groups. 5-year disease survival rate was also not significantly different between the groups. 50 Gy can be considered the appropriate dose for postoperative cervical irradiation. Abstract: Objectives: In patients with advanced oral squamous cell carcinoma (OSCC), surgical treatment is often administered in combination with radiotherapy-based postoperative adjuvant therapy. The aim of the present study was to determine the most appropriate dose by comparing patient outcomes between doses of 50- and 66-Gy for postoperative cervical irradiation. Materials and methods: This retrospective study included patients who underwent postoperative cervical irradiation following neck dissection for OSCC with lymph nodes metastases, and their primary lesions were controlled. They were divided into the 50- and 66-Gy irradiation groups and were examined for sex, age, primary lesion site, tumor/node/metastasis stage, initial treatment for primary cancer, neck dissection procedure, number of metastatic lymph nodes, presence or absence of extranodal extension (ENE), concomitant anticancer agents, and therapeutic outcomes. Results: A total of 78 patients met the clinical criteria for study enrollment. The 50- and 66-Gy postoperative cervical irradiation groups included 40 and 38 patients, with neck dissection performed at 45 and 38 sites, respectively. Cervical control rate was 97.5% and 97.3% in the 50- and 66-Gy irradiation groups ( p  = 0.74). The cumulative disease-specific 5-year survival rate was 85.6% and 88.3%, respectively, with no significant difference ( p  = 0.64). Conclusion: The findings of our study indicate that the irradiation dose of 50 Gy is appropriate for postoperative cervical irradiation in patients with OSCC.